2007
DOI: 10.1103/physrevb.76.220410
|View full text |Cite
|
Sign up to set email alerts
|

Probing the role of the barrier layer in magnetic tunnel junction transport

Abstract: Magnetic tunnel junctions with a ferrimagnetic barrier layer have been studied to understand the role of the barrier layer in the tunneling process -a factor that has been largely overlooked until recently. Epitaxial oxide junctions of highly spin polarized La 0.7 Sr 0.3 MnO 3 and Fe 3 O 4 electrodes with magnetic NiMn 2 O 4 (NMO) insulating barrier layers provide a magnetic tunnel junction system in which we can probe the effect of the barrier by comparing junction behavior above and below the Curie temperatu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
35
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 16 publications
(25 reference statements)
2
35
0
Order By: Relevance
“…19 As has been explained in similar Fe 3 O 4 -based junctions, 4,20 we attribute this decrease in JMR at low temperatures to a suppressed Verwey metal-insulator transition of the Fe 3 O 4 thin film electrode, which is consistent with the temperature dependence of the junction resistance. While bulk Fe 3 O 4 undergoes this transition at 120 K, it is common for epi- taxial Fe 3 O 4 films to show a more suppressed Verwey transition with less abrupt changes in resistivity.…”
Section: B Temperature Dependencesupporting
confidence: 79%
See 2 more Smart Citations
“…19 As has been explained in similar Fe 3 O 4 -based junctions, 4,20 we attribute this decrease in JMR at low temperatures to a suppressed Verwey metal-insulator transition of the Fe 3 O 4 thin film electrode, which is consistent with the temperature dependence of the junction resistance. While bulk Fe 3 O 4 undergoes this transition at 120 K, it is common for epi- taxial Fe 3 O 4 films to show a more suppressed Verwey transition with less abrupt changes in resistivity.…”
Section: B Temperature Dependencesupporting
confidence: 79%
“…5 Such interfacial Mn cation migration effects could also be the reason for the overall lower JMR values of the NFO junctions compared to the paramagnetic NMO junctions previously studied. 4 It is consistent with Mn already present in the NMO barrier layer, resulting in a smaller driving force for Mn of the LSMO to migrate across the interface into the spinelstructure barrier layer, resulting in larger LSMO interfacial spin polarization values and higher JMR values for a given temperature.…”
supporting
confidence: 70%
See 1 more Smart Citation
“…[5][6][7][8][9][10][11][12][13][14][15][16] Symmetry mismatch occurs when the interface is formed from two non-isostructural materials such as an orthorhombic film on a cubic substrate, or even materials consisting of different coordination environments.…”
mentioning
confidence: 99%
“…Recently, ferrimagnetic spinel oxides have been identified as spin filter materials for Fe 3 O 4 based magnetic junctions 1,2 . Moreover, it has been shown that the isostructural interface between half-metallic Fe 3 O 4 electrodes and a spinel barrier layer gives rise to significant junction magnetoresistance that surpass previous rvalues found for Fe 3 O 4 based junctions 3 .…”
mentioning
confidence: 99%